The role of catalytic subunit of AMPK in lipid accumulation in Mucor circinelloides WJ11 - Shuxian Pang; Futing Xue; Wu Yang; Hassan Mohamed; Jinghao Zhao; Muhammad Tariq Saeed; Chao Du; Qing Liu; Yuanda Song (Food Bioscience, 2025)

Oxidative stress and inflammation in renal fibrosis: Novel molecular mechanisms and therapeutic targets - Haojie Liu; Xiadan Xiang; Chengqian Shi; Jiaowei Guo; Ting Ran; Jinglian Lin; Futing Dong; Jie Yang; Hua Miao (Chemico-Biological Interactions, 2025)

Flexible 3D printed fibers of novel manganese halides with superior acid/alkali resistance for X-ray imaging and radiation warning - Yunluo Wang; Tianrui Zhou; Jie Chen; Haoming Qin; Jianghua Wu; Zhiyu Qin; Hao Gu; Zesen Gao; Ruifeng Liu; Tingting Ye; Yan Yang; Futing Sun; et al. (Chemical Engineering Journal, 2025)

Selective recovery of gold from waste printed circuit boards leachate by modified gel zeolitic imidazolate framework-8 - Haojun Hou; Shuliang Chen; Rongquan Liu; Yue Lin; Xianzhi Hu; Futing Zi (Journal of Environmental Chemical Engineering, 2025)

BMSC Derived Exosomes Attenuate Apoptosis of Temporomandibular Joint Disc Chondrocytes in TMJOA via PI3K/AKT Pathway - Wenjun Chen; Futing Huang; Baoyi Chen; Huiyi Lin; Guan Luo; Weijun Zhang; Xiaoyu Zhang; Beining Zheng; Ziyi Wang; Shiting Wei; Jiaxin He; Chang Liu (Stem Cell Reviews and Reports, 2025)

Facilitating CO2 methanation over oxygen vacancy-rich Ni/CeO2: Insights into the synergistic effect between oxygen vacancy and metal-support interaction - Wan Yang; Kaizhu Chang; Meng Yang; Xueshuang Yan; Shiju Yang; Yongjun Liu; Guowei Wang; Futing Xia; Huimin Wang; Qiulin Zhang (Chemical Engineering Journal, 2024)

Molecular mechanism of TRIM32 in antiviral immunity in rainbow trout (Oncorhynchus mykiss) - Mengmeng Zhang; Jinhui Sun; Futing Zhang; Yingrui Zhang; Mian Wu; Weiliang Kong; Xueting Guan; Min Liu (Fish & Shellfish Immunology, 2024)

Increases in macroaggregate fractions following organic fertilizer application decrease microbial-driven CO2 release - Zewen Hei; Stefan Geisen; Jiayu Shao; Yi Yang; Futing Liu; Shunran Hu; Hongyan Zhang; Jan Kammenga; Yongliang Chen (Applied Soil Ecology, 2024)

Permafrost carbon cycle and its dynamics on the Tibetan Plateau - Leiyi Chen; Guibiao Yang; Yuxuan Bai; Jinfeng Chang; Shuqi Qin; Futing Liu; Mei He; Yutong Song; Fan Zhang; Josep Peñuelas; Biao Zhu; Guoying Zhou; et al. (Science China Life Sciences, 2024)

Two phenolic acids altered the rhizosphere microbial community of Panax notoginseng and promoted potential pathogen growth - Yuyan Liu; Jinmiao Chen; Zhidan Liu; Yunlin Wei; Xiaoran Li; Futing Zi; Yong Tan (Physiological and Molecular Plant Pathology, 2024)

Patterns and drivers of prokaryotic communities in thermokarst lake water across Northern Hemisphere - Luyao Kang; Leiyi Chen; Ziliang Li; Jianjun Wang; Kai Xue; Ye Deng; Manuel Delgado‐Baquerizo; Yutong Song; Dianye Zhang; Guibiao Yang; Wei Zhou; Xuning Liu; et al. (Global Ecology and Biogeography, 2023)
Aim The formation of thermokarst lakes could make a large amount of carbon accessible to microbial degradation, potentially intensifying the permafrost carbon‐climate feedback via carbon dioxide/methane emissions. Because of their diverse functional roles, prokaryotes could strongly mediate biogeochemical cycles in thermokarst lakes. However, little is known about the large‐scale patterns and drivers of these communities. Location Permafrost regions in the Northern Hemisphere. Time period Present day. Major taxa studied Prokaryotes. Methods Based on a combination of large‐scale measurements on the Tibetan Plateau and data syntheses in pan‐Arctic regions, we constructed a comprehensive dataset of 16S rRNA sequences from 258 thermokarst lakes across Northern Hemisphere permafrost regions. We also used the local contributions to beta diversity (LCBD) to characterize the variance of prokaryotic species composition and screened underlying drivers by conducting a random forest modelling analysis. Results Prokaryotes in thermokarst lake water were dominated by the orders Burkholderiales, Micrococcales, Flavobacteriales and Frankiales. The relative abundance of dominant taxa was positively associated with dissolved organic matter (DOM) properties, especially for the chromophoric/aromatic compounds. Microbial structure differed between high‐altitude and high‐latitude thermokarst lakes, with the dominance of Flavobacterium in high‐altitude lakes, and the enrichment of Polynucleobacter in high‐latitude lakes. More importantly, climatic variables were among the main drivers shaping the large‐scale variation of prokaryotic communities. Specifically, mean annual precipitation was the best predictor for prokaryotic beta diversity across the Northern Hemisphere, as well as in the high‐altitude permafrost regions, while mean annual air temperature played a key role in the high‐latitude thermokarst lakes. Main conclusions Our findings demonstrate significant associations between dominant taxa and DOM properties, as well as the important role of climatic factors in affecting prokaryotic communities. These findings suggest that climatic change may alter DOM conditions and induce dynamics in prokaryotic communities of thermokarst lake water in the Northern Hemisphere.

Accelerated organic matter decomposition in thermokarst lakes upon carbon and phosphorus inputs - Ziliang Li; Weijie Xu; Luyao Kang; Yakov Kuzyakov; Leiyi Chen; Mei He; Futing Liu; Dianye Zhang; Wei Zhou; Xuning Liu; Yuanhe Yang (Global Change Biology, 2023)
Mineralization of dissolved organic matter (DOM) in thermokarst lakes plays a non‐negligible role in the permafrost carbon (C) cycle, but remains poorly understood due to its complex interactions with external C and nutrient inputs (i.e., aquatic priming and nutrient effects). Based on large‐scale lake sampling and laboratory incubations, in combination with 13 C‐stable‐isotope labeling, optical spectroscopy, and high‐throughput sequencing, we examined large‐scale patterns and dominant drivers of priming and nutrient effects of DOM biodegradation across 30 thermokarst lakes along a 1100‐km transect on the Tibetan Plateau. We observed that labile C and phosphorus (P) rather than nitrogen (N) inputs stimulated DOM biodegradation, with the priming and P effects being 172% and 451% over unamended control, respectively. We also detected significant interactive effects of labile C and nutrient supply on DOM biodegradation, with the combined labile C and nutrient additions inducing stronger microbial mineralization than C or nutrient treatment alone, illustrating that microbial activity in alpine thermokarst lakes is co‐limited by both C and nutrients. We further found that the aquatic priming was mainly driven by DOM quality, with the priming intensity increasing with DOM recalcitrance, reflecting the limitation of external C as energy sources for microbial activity. Greater priming intensity was also associated with higher community‐level ribosomal RNA gene operon ( rrn ) copy number and bacterial diversity as well as increased background soluble reactive P concentration. In contrast, the P effect decreased with DOM recalcitrance as well as with background soluble reactive P and ammonium concentrations, revealing the declining importance of P availability in mediating DOM biodegradation with enhanced C limitation but reduced nutrient limitation. Overall, the stimulation of external C and P inputs on DOM biodegradation in thermokarst lakes would amplify C‐climate feedback in this alpine permafrost region.

JAM-A Overexpression in Human Umbilical Cord-Derived Mesenchymal Stem Cells Accelerated the Angiogenesis of Diabetic Wound By Enhancing Both Paracrine Function and Survival of Mesenchymal Stem Cells - Futing Shu; Jianyu Lu; Wei Zhang; Hongchao Huang; Jiezhi Lin; Luofeng Jiang; Wenzhang Liu; Tianyi Liu; Shichu Xiao; Yongjun Zheng; Zhaofan Xia (Stem Cell Reviews and Reports, 2023)

Different effects of six saponins on the rhizosphere soil microorganisms of Panax notoginseng - Limei Bao; Yuyan Liu; Jinmiao Chen; Yafang Ding; Junjie Shang; Jinhua Li; Yunlin Wei; Futing Zi; Yong Tan (Plant and Soil, 2023)

Patterns and drivers of anaerobic nitrogen transformations in sediments of thermokarst lakes - Chao Mao; Yutong Song; Yunfeng Peng; Luyao Kang; Ziliang Li; Wei Zhou; Xuning Liu; Futing Liu; Guibing Zhu; Yuanhe Yang (Global Change Biology, 2023)
Significant attention has been given to the way in which the soil nitrogen (N) cycle responds to permafrost thaw in recent years, yet little is known about anaerobic N transformations in thermokarst lakes, which account for more than one‐third of thermokarst landforms across permafrost regions. Based on the N isotope dilution and tracing technique, combined with qPCR and high‐throughput sequencing, we presented large‐scale measurements of anaerobic N transformations of sediments across 30 thermokarst lakes over the Tibetan alpine permafrost region. Our results showed that gross N mineralization, ammonium immobilization, and dissimilatory nitrate reduction rates in thermokarst lakes were higher in the eastern part of our study area than in the west. Denitrification dominated in the dissimilatory nitrate reduction processes, being two and one orders of magnitude higher than anaerobic ammonium oxidation (anammox) and dissimilatory nitrate reduction to ammonium (DNRA), respectively. The abundances of the dissimilatory nitrate reduction genes ( nirK , nirS , hzsB , and nrfA ) exhibited patterns consistent with sediment N transformation rates, while α diversity did not. The inter‐lake variability in gross N mineralization and ammonium immobilization was dominantly driven by microbial biomass, while the variability in anammox and DNRA was driven by substrate supply and organic carbon content, respectively. Denitrification was jointly affected by nirS abundance and organic carbon content. Overall, the patterns and drivers of anaerobic N transformation rates detected in this study provide a new perspective on potential N release, retention, and removal upon the formation and development of thermokarst lakes.

Clarifying sleep characteristics and analyzing risk factors of sleep disorders to promote a predictive, preventive, and personalized medicine in patients with burn scars - Huazhen Liu; Futing Shu; Chao Ji; Haiting Xu; Zixuan Zhou; Yuxiang Wang; Haojie Gao; Pengfei Luo; Yongjun Zheng; Kaiyang Lv; Shichu Xiao (EPMA Journal, 2023)

Flotation performance and adsorption mechanism of sodium lauroyl sarcosinate on lead ion-modified bastnaesite surfaces - Yang Liu; Zhicong Wei; Xianzhi Hu; Futing Zi (Minerals Engineering, 2023)

Phosphorus rather than nitrogen regulates ecosystem carbon dynamics after permafrost thaw - Guibiao Yang; Yunfeng Peng; Benjamin W. Abbott; Christina Biasi; Bin Wei; Dianye Zhang; Jun Wang; Jianchun Yu; Fei Li; Guanqin Wang; Dan Kou; Futing Liu; et al. (Global Change Biology, 2021)
Ecosystem carbon (C) dynamics after permafrost thaw depends on more than just climate change since soil nutrient status may also impact ecosystem C balance. It has been advocated that nitrogen (N) release upon permafrost thaw could promote plant growth and thus offset soil C loss. However, compared with the widely accepted C‐N interactions, little is known about the potential role of soil phosphorus (P) availability. We combined 3‐year field observations along a thaw sequence (constituted by four thaw stages, i.e., non‐collapse and 5, 14, and 22 years since collapse) with an in‐situ fertilization experiment (included N and P additions at the level of 10 g N m −2 year −1 and 10 g P m −2 year −1 ) to evaluate ecosystem C‐nutrient interactions upon permafrost thaw. We found that changes in soil P availability rather than N availability played an important role in regulating gross primary productivity and net ecosystem productivity along the thaw sequence. The fertilization experiment confirmed that P addition had stronger effects on plant growth than N addition in this permafrost ecosystem. These two lines of evidence highlight the crucial role of soil P availability in altering the trajectory of permafrost C cycle under climate warming.

Large‐scale evidence for microbial response and associated carbon release after permafrost thaw - Yongliang Chen; Futing Liu; Luyao Kang; Dianye Zhang; Dan Kou; Chao Mao; Shuqi Qin; Qiwen Zhang; Yuanhe Yang (Global Change Biology, 2021)
Permafrost thaw could trigger the release of greenhouse gases through microbial decomposition of the large quantities of carbon (C) stored within frozen soils. However, accurate evaluation of soil C emissions from thawing permafrost is still a big challenge, partly due to our inadequate understanding about the response of microbial communities and their linkage with soil C release upon permafrost thaw. Based on a large‐scale permafrost sampling across 24 sites on the Tibetan Plateau, we employed meta‐genomic technologies (GeoChip and Illumina MiSeq sequencing) to explore the impacts of permafrost thaw (permafrost samples were incubated for 11 days at 5°C) on microbial taxonomic and functional communities, and then conducted a laboratory incubation to investigate the linkage of microbial taxonomic and functional diversity with soil C release after permafrost thaw. We found that bacterial and fungal α diversity decreased, but functional gene diversity and the normalized relative abundance of C degradation genes increased after permafrost thaw, reflecting the rapid microbial response to permafrost thaw. Moreover, both the microbial taxonomic and functional community structures differed between the thawed permafrost and formerly frozen soils. Furthermore, soil C release rate over five month incubation was associated with microbial functional diversity and C degradation gene abundances. By contrast, neither microbial taxonomic diversity nor community structure exhibited any significant effects on soil C release over the incubation period. These findings demonstrate that permafrost thaw could accelerate C emissions by altering the function potentials of microbial communities rather than taxonomic diversity, highlighting the crucial role of microbial functional genes in mediating the responses of permafrost C cycle to climate warming.

Altered microbial structure and function after thermokarst formation - Futing Liu; Dan Kou; Yongliang Chen; Kai Xue; Jessica G. Ernakovich; Leiyi Chen; Guibiao Yang; Yuanhe Yang (Global Change Biology, 2021)
Permafrost thaw could induce substantial carbon (C) emissions to the atmosphere, and thus trigger a positive feedback to climate warming. As the engine of biogeochemical cycling, soil microorganisms exert a critical role in mediating the direction and strength of permafrost C‐climate feedback. However, our understanding about the impacts of thermokarst (abrupt permafrost thaw) on microbial structure and function remains limited. Here we employed metagenomic sequencing to analyze changes in topsoil (0–15 cm) microbial communities and functional genes along a permafrost thaw sequence (1, 10, and 16 years since permafrost collapse) on the Tibetan Plateau. By combining laboratory incubation and a two‐pool model, we then explored changes in soil labile and stable C decomposition along the thaw sequence. Our results showed that topsoil microbial α‐diversity decreased, while the community structure and functional gene abundance did not exhibit any significant change at the early stage of collapse (1 year since collapse) relative to non‐collapsed control. However, as the time since the collapse increased, both the topsoil microbial community structure and functional genes differed from the control. Abundances of functional genes involved in labile C degradation decreased while those for stable C degradation increased at the late stage of collapse (16 years since collapse), largely driven by changes in substrate properties along the thaw sequence. Accordingly, faster stable C decomposition occurred at the late stage of collapse compared to the control, which was associated with the increase in relative abundance of functional genes for stable C degradation. These results suggest that upland thermokarst alters microbial structure and function, particularly enhances soil stable C decomposition by modulating microbial functional genes, which could reinforce a warmer climate over the decadal timescale.

Warming effects on permafrost ecosystem carbon fluxes associated with plant nutrients - Fei Li; Yunfeng Peng; Susan M. Natali; Kelong Chen; Tianfeng Han; Guibiao Yang; Jinzhi Ding; Dianye Zhang; Guanqin Wang; Jun Wang; Jianchun Yu; Futing Liu; et al. (Ecology, 2017)
Large uncertainties exist in carbon (C)‐climate feedback in permafrost regions, partly due to an insufficient understanding of warming effects on nutrient availabilities and their subsequent impacts on vegetation C sequestration. Although a warming climate may promote a substantial release of soil C to the atmosphere, a warming‐induced increase in soil nutrient availability may enhance plant productivity, thus offsetting C loss from microbial respiration. Here, we present evidence that the positive temperature effect on carbon dioxide ( CO 2 ) fluxes may be weakened by reduced plant nitrogen (N) and phosphorous (P) concentrations in a Tibetan permafrost ecosystem. Although experimental warming initially enhanced ecosystem CO 2 uptake, the increased rate disappeared after the period of peak plant growth during the early growing season, even though soil moisture was not a limiting factor in this swamp meadow ecosystem. We observed that warming did not significantly affect soil extractable N or P during the period of peak growth, but decreased both N and P concentrations in the leaves of dominant plant species, likely caused by accelerated plant senescence in the warmed plots. The attenuated warming effect on CO 2 assimilation during the late growing season was associated with lowered leaf N and P concentrations. These findings suggest that warming‐mediated nutrient changes may not always benefit ecosystem C uptake in permafrost regions, making our ability to predict the C balance in these warming‐sensitive ecosystems more challenging than previously thought.